No Association Between Lipid Profiles and Acne Vulgaris - Khairina Nasution; Imam Budi Putra; Nelva Karmila Jusuf (Cell and BioPharmaceutical Institute, 2018)
Background: Acne vulgaris is a chronic inflammation of pilosebaceous follicle that can spontaneously heal with clinical manifestations such as blackhead, papules, pustules, nodule, and cyst on the face, upper chest, arms, and back. Until now, the effect of lipid metabolism on sebaceous gland secretions in the pathogenesis of acne vulgaris is still under research.Materials and Methods: An analytic observational study with cross sectional design involving 30 acne vulgaris and 30 control subjects was conducted. Blood samples were taken from subjects and lipid profile levels were measured. The data were then statistically analyzed.Results: From this research, there was no significant association between lipid profiles with acne vulgaris. There was not any significant difference between the acne vulgaris and the control subjects for total cholesterol, High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL) and triglyceride levels (p>0.05).Conclusion: There is no significant association between lipid profiles levels and acne vulgaris.Keywords: acne vulgaris, lipid profiles, total cholesterol, HDL, LDL, triglyceride